Linkages between tourist resorts, local food production and the sustainable development goals. Issue 4 (1st July 2021) - Scheyvens, Regina; Laeis, Gabriel
Abstract: The United Nations' Sustainable Development Goals (SDGs), ratified in 2015, are set to guide global development through to 2030. As an industry, tourism receives considerable attention in development discussions and in planning for development in the Global South, particularly in small island developing states (SIDS). A number of authors see particular prospects in the area of food producer linkages with the tourism industry, based on the notion that it should be possible to enhance both local food systems and tourism industries in SIDS by putting more local food on the menu. In this article, we test the assumption that building strong linkages between tourism and food production systems, especially agriculture and fisheries, is possible, and desirable, and would lead to more sustainable development. We do this by drawing on data from research in hotel kitchens and on farms in the South Pacific country of Fiji. When reflecting on the Fijian data in light of SDGs 2, 12 and 14, it is apparent that there are considerable constraints to developing food-tourism linkages in a way that will deliver more sustainable development in future. While 'island night' menus do use a lot of local produce, and small numbers of guests enjoy consuming Fijian foods at fine dining restaurants, incorporating local produce into mainstream resort menus had been difficult for chefs. Overall, the way large-scale multinational resorts are structured in terms of their food requirements does not make them ideal partners for food producers in developing countries, particularly SIDS.